Selenium status in a group of schoolchildren from the region of Madrid, Spain. (17th May 2013) - Navia, B.; Ortega, R. M.; Perea, J. M.; Aparicio, A.; López‐Sobaler, A. M.; Rodríguez‐Rodríguez, E.; ,
Abstract: Background: To assess the selenium status of a group of schoolchildren from the Region of Madrid, Spain. Methods: Study subjects comprised 483 children (216 boys and 267 girls) aged between 8 and 13 years. Selenium intake was determined using a 3‐day food record. The foods consumed were transformed into energy and nutrients, and the selenium intake was compared with that recommended. Serum selenium levels were also recorded. Results: Mean (SD) selenium intake [91.0 (25.2) μg day −1 ] was above the recommended level in 99.4% of subjects; the main dietary sources were cereals, meats, fish and milk products. The serum selenium concentration [mean (SD) 71.1 (14.4) μg L −1 ], however, was <60 μg L −1 in 13.9% of subjects, and <45 μg L −1 in 5.6%. The serum selenium concentration correlated with the selenium intake ( r = 0.169; P < 0.05). Children with a serum selenium concentration of <75 μg L −1 had significantly smaller selenium intakes than those with a serum concentration of ≥75 μg L −1 . Conclusions: Although selenium intake was generally above that recommended, the serum selenium concentration of the children could be improved. This could be achieved by increasing the relative consumption of cereals and other selenium rich foods such as fish.